Top-emitting 940-nm thin-film VCSELs transferred onto aluminum heatsinks - Moon, Sunghyun; Yun, Yeojun; Lee, Minhyung; Kim, Donghwan; Choi, Wonjin; Park, Ji Yong; Lee, Jaejin (Scientific Reports, 2022)
Thin-film vertical cavity surface emitting lasers (VCSELs) mounted onto heatsinks open up the way toward low-power consumption and high-power operation, enabling them to be widely used for energy saving high-speed optical data communication and three-dimensional sensor applications. There are two conventional VCSEL polarity structures: p-on-n and n-on-p polarity. The former is more preferably used owing to the reduced series resistance of n-type bottom distributed Bragg reflection (DBR) as well as the lower defect densities of n-type GaAs substrates. In this study, the p-on-n structures of thin-film VCSELs, including an etch stop layer and a highly n-doped GaAs ohmic layer, were epitaxially grown in upright order by using low-pressure metalorganic chemical vapor deposition (LP-MOCVD). The p-on-n structures of thin-film VCSELs were transferred onto an aluminum heatsink via a double-transfer technique, allowing the top-emitting thin-film VCSELs to keep the p-on-n polarity with the removal of the GaAs substrate. The threshold current (Ith) and voltage (Vth) of the fabricated top-emitting thin-film VCSELs were 1 mA and 2.8 V, respectively. The optical power was 7.7 mW at a rollover point of 16.1 mA.